How to do things with notes: The embodied socio-material performativity of sticky notes. (September 2021) - Matthews, Ben; Khan, Awais Hameed; Snow, Stephen; Schlosser, Paul; Salisbury, Isaac; Matthews, Sarah
Abstract : This paper presents a detailed analysis of the uses of sticky notes in a range of design-oriented activities, from three different projects. The paper makes two principal contributions. First, it introduces a socio-material analytic for the study of design materials, and exemplifies this analysis with respect to video data of designers' uses of sticky notes. Second, it illustrates how the material properties of sticky notes come to have interactional consequences in the performance of particular social actions. Four general thematic considerations emerge from this socio-material analysis of sticky notes: (1) a reappreciation of the embodiment of space, ownership and actions-with-notes; (2) the interactional history of notes; (3) the social and conceptual inertia of gestalt contextures; and (4) the unity of the social, material and conceptual in embodied design activity. Highlights: Material properties of sticky notes are used in the performance of social actions. A socio-material analytic perspective is introduced and exemplified. The social and material aspects of sticky notes are mutually constitutive.